0257 Prescription Sleep Aid Use Impacts Family Functioning for Families with Grandparents Raising Grandchildren. (12th April 2019) - Pandey, Abhishek; Cooper, Lawrence; Carter, Shima; Rosenthal, Michelle; Littlewood, Kerry
Abstract: Introduction: One in ten grandparents live with their grandchildren (GRG). GRGs are more likely to live in poverty, work at least part time, and have disability status than grandparents with no coresident grandchildren. No studies have explored if prescription sleep aid use for GRG may be related to the child's sleep or family functioning. This study examines prescribed sleep aid use for GRGs and how it may be related to the child's sleep and family functioning. Methods: This study used twelve month follow up data from the KIN-Tech 2012 Fostering Connections federal demonstration project funded by the US Children's Bureau. A random selection of one hundred GRGs with self-reported twelve month follow up assessments including the Protective Factors Survey (Counts, 2010) to measure family functioning for themselves and the children in their care. ANOVAs were used to compare prescription sleep aid use, chronic conditions with family functioning. Results: Participants in this study included grandmothers (88%) from low income households (m=24, 000), 46 years of age, single (66%), African American (46%). Forty-one percent (n=43) of caregivers reported troubled sleep, with 41% (n=43) indicated that caregiving impacts their sleep. Twenty five percent of caregivers (n=25) take sleep aids. Caregivers with Asthma [F(2, 90)=4.11, p<.01] and other chronic conditions [F(2, 89)=3.53, p<.05] are more likely to raise children who have been prescribed sleep aids, especially medication for ADHD. Caregivers who are prescribed sleep aids are more likely to raise children who are prescribed sleep aids [F(2, 92)=3.13, p<.05] and report less resilient family functioning [F(2.92)=4.1, p<.01]. Conclusion: One of first studies to examine how GRG prescribed sleep aid use is related to prescribed child sleep aid and overall family functioning. Results suggest that caregivers who are prescribed sleep aids are more likely to suffer from chronic conditions and raise children who are prescribed sleep aids and have less resilient family functioning. Future studies need to examine the impact of sleep aids that are being used and how they impact family functioning on a day-to-day level. Support (If Any): US Children's Bureau